From Guilt to Forgive the Self : Self Forgiveness pada Klien Dewasa di Balai Pemasyarakatan Kelas I Malang: Indonesia - Nugraheni, Ayu Jesika; Nurmala, Sukma (Interaktif : Jurnal Ilmu-Ilmu Sosial, 2024)
Fraud is one of the criminal acts that often occurs in Indonesia. The individuals involved must lose their freedom. Then they will receive guidance from the Correctional Center (Bapas) to return to society. This research aims to determine the dynamics of the self-forgiveness process in adult clients with fraud cases at the Class I Malang Correctional Center (Bapas). This research method is qualitative phenomenology. Data was collected through semi-structured interviews, unstructured observation and documentation studies. The data will then be verified by source triangulation. The collected data was analyzed using Miles & Huberman analysis. The research results show that the self-forgiveness process experienced by each person is different. There were feelings of guilt in both informants, which was a factor in repeating the stages of self-forgiveness. As a result, the two informants had different movements in the self-forgiveness process. Bapas can provide support in the form of training and education regarding self-forgiveness to adult clients so that self-forgiveness can be implemented and can help adult clients live their lives again. Keywords: Bapas, fraud, self forgiveness